Kinder in Jugendverbänden Eine empirische Untersuchung zu Strukturen, Konzepten und Motiven im Kontext der gesellschaftlichen Debatten um Inklusion - Voigts, Gunda (Verlag Barbara Budrich, 2015)
In this book, Gunda Voigts dedicates herself to the first systematic research into the topics of "children in youth associations" and "practice of inclusion in child and youth work". Those involved in research, politics and practice in child and youth work who want to deal with the current requirements of a consistent inclusion perspective in the sense of the UN Disability Rights Convention for this field of action will receive a valuable overview of the current status of the discussion. The results of current children's surveys are included as well as a fundamental, comprehensive analysis of previous youth association studies. With the help of qualitative expert interviews and a quantitative questionnaire survey, the author can make reliable statements about the actual reality of inclusion in youth organizations and classify the field of child and youth work in the current inclusion debate. For everyone who is involved in research, politics or practice, as an employee in youth associations, municipalities or child and youth welfare institutions, with current issues of child and youth work or in particular extracurricular offers for children or the importance of inclusion for their field of work , this book offers many new insights and suggestions.